Novel Even Beam Splitters Based on Subwavelength Binary Simple Periodic Rectangular Structure - Huang, Haixuan; Ruan, Shuangchen; Yang, Tuo; Xu, Ping (Nano-Micro Letters, 2015)
In this paper, a novel method of a subwavelength binary simple periodic rectangular structure is presented to realize even beam splitting by combining the rigorous couple-wave analysis with the genetic algorithm. Several even splitters in the terahertz region were designed and one of the silicon-based beam splitters designed to separate one incident beam into four emergent beams has total efficiency up to 92.23 %. Zero-order diffraction efficiency was reduced to less than 0.192 % and the error of uniformity decreased to 6.51 × 10−6. These results break the limitation of even beam splitting based on the traditional scalar theory. In addition, the effects of the incident angle, wavelength, as well as the polarizing angle on the diffraction efficiency and uniformity were also investigated.